El uso de la inteligencia artificial en la toma de decisiones legales en los procesos civiles: Implicaciones éticas y jurídicas. - Lara Noboa, Camila Soledad (2024)
The study entitled “The Use of Artificial Intelligence in Legal Decision Making in Civil Proceedings: Ethical and Legal Implications” analyzes the use of artificial intelligence (AI) in the civil legal field, assessing its scope and limitations, as well as its ethical and legal challenges. The research objectives include investigating the scope and limitations of AI in civil justice, assessing the associated ethical challenges, and analyzing current regulation to propose ethical guidelines. The methodology employed comprises several methods, including deductive, legal-analytical and dogmatic, applied in the Civil Judicial Unit and the Provincial Court of Justice of Chimborazo. The results show that AI can improve efficiency and uniformity in law enforcement, although it presents risks such as algorithmic bias and dehumanization of judicial processes. Transparency and accountability are essential for the acceptance and legitimacy of AI-assisted decisions. The research concludes that while AI can positively transform the administration of civil justice, it is crucial to address its ethical implications and establish a robust regulatory framework to mitigate risks and maximize benefits.